Ruang Lingkup E-Modul Analisa Desain Sistem Informasi Bermuatan THK Dalam Meningkatkan Sikap Sosial - Suryanti Kusuma, Aniek; Parwati, Ni Nyoman; Tegeh, I made; Sudarma, I Komang (UHN IGB Sugriwa Denpasar, 2023)
The low social attitude of students towards the surrounding environment is a challenge in itself. This study aims to study the effectiveness of e-modules in improving students' social attitudes with the outside learning environment, especially in the Information System Design Analysis (ADSI) course. This course analyzes and designs information systems in IT projects. THK is a local Balinese culture that is essentially balanced and harmonious. The development of THK courses for ADSI aims to improve students' social attitudes towards the environment outside of academics. During the COVID-19 pandemic, the learning model widely used was the hybrid learning model. Teaching materials suitable for use in the hybrid learning model are electronic modules (e-modules). This learning media is the latest innovation from the print module, so this e-module can be accessed with the help of computers and cellphones that have been integrated with supporting software. The advantages of e-modules compared to print modules are interactive, easy to navigate, can display images, audio, video and animation. Equipped with formative tests that allow automatic feedback, the e-module is perfect for ADSI courses